2021
DOI: 10.1007/s11739-021-02702-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of influenza vaccine on COVID-19 mortality: a retrospective study

Abstract: It has been proposed that vaccines may exert an unspecific protective effect against infectious agents, different than expected. Coronavirus disease 2019 (COVID-19) is a pandemic infection with high mortality in older patients due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The high number of vaccinations may be one of the reasons why children show a lower susceptibility to SARS-CoV-2 infection and milder severity when compared to adults. We have designed a study aimed at investigating whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
60
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 26 publications
9
60
1
7
Order By: Relevance
“…Different studies have shown a significant inverse association between influenza vaccination and severity of COVID-19 in terms of hospitalized patients, ICU admissions, and deaths attributable to the virus [5][6][7], raising the possibility that the influenza vaccine may activate the immune system sufficiently to prevent infection (by any virus) in a window after vaccination [4]. It was suggested that this could occur if the vaccine is able to sufficiently stimulate innate immunity against respiratory viruses, including SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have shown a significant inverse association between influenza vaccination and severity of COVID-19 in terms of hospitalized patients, ICU admissions, and deaths attributable to the virus [5][6][7], raising the possibility that the influenza vaccine may activate the immune system sufficiently to prevent infection (by any virus) in a window after vaccination [4]. It was suggested that this could occur if the vaccine is able to sufficiently stimulate innate immunity against respiratory viruses, including SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the induction of trained immunity and its effects in the pathogenesis of autoinflammatory diseases has been an important tool in the management of serious viral infections, such as COVID-19 [ 191 ]. Based on this evidence, other researchers have also evaluated the role of influenza vaccination as an indirect system useful to increase the body’s defenses against COVID-19 [ 192 , 193 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was no obvious understanding of the mechanism behind this relationship. 26 , 27 , 28 , 29 , 30 As a consequence of the similarity of the clinical presentation between the two diseases and the possible correlation between the reduction of COVID-19 disease mortality rate in influenza vaccinated patients, the rational of the importance of increasing the coverage rate of influenza vaccine has been emerged. [ 26 , 30 ] Increasing the rate of influenza vaccine uptake could decrease the burden on health care facilities associated with seasonal influenza infections, and could help to decrease COVID-19 mortality rates.…”
Section: Introductionmentioning
confidence: 99%